0
$\begingroup$

Let the sequence $\{a_n\}_{n\ge0}$ be recursively defined as follows: $$a_0=0,\,\forall k\ge1(a_k=a_{k-1}+2k+1).$$ Using mathematical induction, prove that this sequence satisfies the following equation:$$\forall n\ge0(a_n=n(n+2)).$$

I have done the basis step as shown below, but still struggling to solve the inductive step.

Basis step: for $n=0$, $a_0=0=0(0+2)$.

$\endgroup$
0
$\begingroup$

We want to prove if $a_{k-1}=(k-1)(k+1)$ then $a_k=k(k+2)$. By the inductive hypothesis,$$a_k=(k-1)(k+1)+2k+1=\cdots$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.